Culture-Free Leadership Effectiveness Versus Moderators of Leadership Behavior: An Extension and Test of Kerr and Jermier's “Substitutes for Leadership” Model in Taiwan - Farh, Jiing-Lih; Podsakoff, Philip M.; Cheng, Bor-Shiuan (Journal of International Business Studies, 1987)
This study was designed to examine whether several situational variables serve as moderators of the effects of leader reward and punishment behaviors for Taiwanese workers. Contrary to what would be expected from Kerr and Jermier's (1978) substitutes for leadership model, none of the situational variables was found to reverse (1) the positive relationship between leader contingent reward behavior and subordinate performance or satisfaction, or (2) the generally negative relationship between leader noncontingent punishment behavior and these subordinate criterion variables. Potential limitations of these findings, and their implications for the study of leadership effectiveness across cultures are then discussed.